2009
DOI: 10.1186/1756-0500-2-233
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in bacterial shedding and improvement in milk production in dairy farms after the use of a new inactivated paratuberculosis vaccine in a field trial

Abstract: BackgroundParatuberculosis vaccination has been in use in some regions for many decades, but results have not been widely spread. A new Mycobacterium avium subsp. paratuberculosis (MAP) killed vaccine was studied in relationship with its effects on fecal shedding and milk production in four farms while other two were kept as controls submitted to a test and cull scheme.FindingsFecal detection (n = 1829) and milking records (n = 2413) have been analyzed after two (5 herds) and four (1 herd) years of the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 9 publications
1
52
0
2
Order By: Relevance
“…MAP DNA detection based on the amplification of the specific IS900 insertion sequence was carried out using the ADIAVET ® PARATB Real Time commercial kit (Adiagene, Saint Brieuc, France) and the ABI Prism 7000 Sequence Detection System (Applied Biosystems, Foster City, CA, USA) as previously described (Juste et al, 2009). Samples were scored positive if their threshold cycle (Ct) was less than 40.00.…”
Section: Microbiological Findings: Map Isolation and Is900 Amplificationmentioning
confidence: 99%
“…MAP DNA detection based on the amplification of the specific IS900 insertion sequence was carried out using the ADIAVET ® PARATB Real Time commercial kit (Adiagene, Saint Brieuc, France) and the ABI Prism 7000 Sequence Detection System (Applied Biosystems, Foster City, CA, USA) as previously described (Juste et al, 2009). Samples were scored positive if their threshold cycle (Ct) was less than 40.00.…”
Section: Microbiological Findings: Map Isolation and Is900 Amplificationmentioning
confidence: 99%
“…Briefly, 300 mL of the supernatant obtained after the cell disruption stage were transferred to Eppendorf tubes containing 20 mL of Lysis 2 buffer, firstly incubated at 70 ± 2 ºC for 10 min and next at 95 ± 2 °C for 15 min. The amplification of specific IS900 MAP DNA by using Adiavet® Map DNA extraction and detection kit (Adiagene, Saint Brieuc, France) and the ABI Prism 7000 Sequence Detection System (Applied Biosystems, Forter City, CA, USA) was carried out as previously described (Juste et al, 2009). Samples were scored as positive when reaching a threshold cycle (Ct) value of 40.00 or lower.…”
Section: Map Isolation From Tissues: Culture and Real Time Pcr (Rtpcr)mentioning
confidence: 99%
“…Then, an adapted protocol for tissue samples was performed using Adiapure® MAP DNA extraction and purification kit (Adiagene, Saint Brieuc, France). The protocol was carried out as described for fecal samples (Juste et al, 2009) but including an additional chemical lysis stage. Briefly, 300 mL of the supernatant obtained after the cell disruption stage were transferred to Eppendorf tubes containing 20 mL of Lysis 2 buffer, firstly incubated at 70 ± 2 ºC for 10 min and next at 95 ± 2 °C for 15 min.…”
Section: Map Isolation From Tissues: Culture and Real Time Pcr (Rtpcr)mentioning
confidence: 99%
“…Although none of the vaccines induced sterile immunity they did slow disease progression and demonstrated that development of a vaccine that induces sterile immunity is feasible (reviewed in (Rosseels and Huygen 2008). Of interest, the studies also revealed the current vaccines can be used therapeutically to reverse immunopathology (Bull et al 2007;Juste et al 2009;Singh et al 2010), an observation first observed by Koch (reviewed in (Burke 1993)). If animals are not too far advanced in clinical disease, the effect can be dramatic with a reversal of pathology (Singh et al 2010).…”
Section: Various Approaches Have Been Taken To Develop a Vaccine Tomentioning
confidence: 88%
“…paratuberculosis (Map) that induces sterile immunity against Johne's disease (JD) or prevents disease progression. These approaches have included development of killed whole vaccines, live attenuated, DNA and subunit vaccines and tests in different animal species (Bull et al 2007;Park et al 2008;Juste et al 2009;Kathaperumal et al 2009;Scandurra et al 2010;Bastida and Juste 2011;Stabel et al 2012;Faisal et al 2013). Although none of the vaccines induced sterile immunity they did slow disease progression and demonstrated that development of a vaccine that induces sterile immunity is feasible (reviewed in (Rosseels and Huygen 2008).…”
Section: Various Approaches Have Been Taken To Develop a Vaccine Tomentioning
confidence: 99%